Lymphangioma of breast and axilla in an adult female: A rare occurrence (Indian Journal of Case Reports, 2019)
Lymphangioma is a developmental condition caused by the failure of lymphatic channels to communicate with the venous system or sequestrated lymphatic channels. Breast and axilla are rare sites for lymphangioma. Very few cases of lymphangioma of breast and axilla have been reported in the literature. Here, we present the case of a 23-year old female presenting with swelling in the right breast and axilla for ten months. Ultrasonography (USG) showed a multiloculated anechoic mass lesion in breast and axilla. Magnetic resonance imaging (MRI) showed multiloculated septate mass homogenously hyperintense on T2 and hypointense on T1. The USG and MRI findings were suggestive of lymphangioma and confirmed on cytology and histopathology. The location and imaging findings were typical of breast lymphangioma.